The Effect of Competence, and Compensation Towards the Performance of Lecturers Nahdlatul University Cirebon - Bahtiar; Bambang Sudaryana (Universitas Djuanda, 2020)
This study aims to analyze the effect of Competence, and Compensation to Lecture performance. This research was conducted at the Nakhdatul Ulama University Cirebon. The samples in this study were all employees, amounting to as much as 50 respondents. This study is a quantitative research and analysis methods of data using multiple linear regression. The results of this study indicate that the variables of Competence, and Compensation significantly influence Lecture performance. In significantly affect the performance of Lecture while variable Competence and Compensation significantly affect the performance of lecturers at a significance level of less than 0.05 or 5%.